Sand Resources on the Inner Continental Shelf of the Cape May Region, New Jersey. - Meisburger,Edward P; Williams,S Jeffress (1980)
About 1,235 square kilometers of the Inner Continental Shelf adjacent to Cape May peninsula was investigated by a seismic reflection and coring survey to obtain geologic information on sea floor and subbottom sand and gravel deposits having suitable characteristics for use as fill in beach nourishment and restoration projects. Water depths in the study area ranged from about 1.5 to 21 meters. A total of 1,258 kilometers of seismic profiles and 104 vibratory cores, ranging in length from 1 to 3.7 meters, were examined. Linear and arcuate shoals are the dominant sea floor features in the region and most appear to be composed of clean, fine to very coarse-grained quartz sand which overlies a flat deposition surface. Several cores penetrating the surface show the underlying material to be a poorly sorted admixture of fine-grained and very coarse-grained sediments that are denser than the modern shelf sands and probably represent a pre-Holocene fluvial deposit. (Author)